2013
DOI: 10.1002/ppul.22904
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide inhibits angiotensin II-induced proliferation and migration of pulmonary arterial smooth muscle cells

Abstract: Pulmonary vascular remodeling, characterized by disordered proliferation and migration of pulmonary arterial smooth muscle cells (PASMCs), is a pathognomonic feature of pulmonary arterial hypertension. Thus, pharmacologic strategy targeting on anti-proliferation and anti-migration of PASMCs may have therapeutic implications for PAH. Here we investigated the effects and underlying mechanisms of B-type natriuretic peptide (BNP) on angiotensin II (Ang II)-induced proliferation and migration of PASMCs. Proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
2
20
0
1
Order By: Relevance
“…Culture media were changed every 3 days and primary cultures of two passages were used in the experiments. The purity of DASMC was confirmed under confocal microscope using immunofluorescence staining for α-smooth muscle actin (>95% of cells stained positive), with typical “hill and valley” appearance and lack of staining for vimentin, as we previously described 20. Serum starvation before experiments was achieved by 1% FBS for 48 h to synchronize cells into quiescence.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Culture media were changed every 3 days and primary cultures of two passages were used in the experiments. The purity of DASMC was confirmed under confocal microscope using immunofluorescence staining for α-smooth muscle actin (>95% of cells stained positive), with typical “hill and valley” appearance and lack of staining for vimentin, as we previously described 20. Serum starvation before experiments was achieved by 1% FBS for 48 h to synchronize cells into quiescence.…”
Section: Methodsmentioning
confidence: 97%
“…Then cells were trypsinized, centrifuged at 1,250 × g for 5 min, washed twice with cold PBS, and treated with RNase A (10 μg/ml). DNA was stained with propidium iodide (50 μg/ml) for 30 min at 37℃, and 5 × 10 3 cells were then analyzed by flow cytometry as we previously described 20.…”
Section: Methodsmentioning
confidence: 99%
“…Atrial natriuretic peptide has been shown to dilate rat DA in vivo [ 23 ]. Our recent study demonstrated that higher B-type natriuretic peptides (BNP) convey anti-remodeling effects in the pulmonary artery SMCs [ 46 ]. Furthermore, in the setting of neonatal intensive care unit, plasma levels of BNP are associated with poor response to indomethacin treatment in preterm infants with PDA [ 44 ].…”
Section: Functional Closurementioning
confidence: 99%
“…Most of the information concerning the effects of BNP on ASM cell proliferation has been obtained from in vitro models. For example, BNP inhibited angiotensin IIinduced smooth muscle cell proliferation, likely mediated by a decreased calcium influx, reduced ROS production and Akt signal transduction[55].…”
mentioning
confidence: 99%